Influence of stress induced microcracks on the tensile fracture behavior of rocks. (December 2018) - Moosavi, Sourena; Scholtès, Luc; Giot, Richard
Abstract: The study characterizes the influence of preferentially oriented microcracks on the tensile fracture behavior of rocks by means of a discrete modeling approach. A series of numerical experiments is performed so as to systematically evaluate the emergent properties of media containing microcracks swarms with predefined intensities and orientations. Emphasis is put on the apparent Young's modulus, tensile strength and fracture toughness. Microcracks swarms reduce the strength of materials, affect their overall brittleness and induce anisotropic behavior. They also directly influence the initiation and propagation of mode I fractures which can deviate from their expected path as a result of branching.